Hydrodynamical simulations of outbursts in protostellar accretion discs - Orellana, Mariana Dominga (2009)
Low mass young stellar objects (YSOs) occasionally display large scale luminosity fluctuations.The standard explanation for these outbursts are global thermalinstabilities in the accretion disc which occur if the inner regions are sufficiently hot for hydrogen to become ionized. However, early models (e.g. Bell & Lin 1994) require extremely low values of the viscosity parameter alpha to reproduce the observed time scales. Armitage et al. (2001) suggested that this issue might be resolved by combining a magnetically layered intermediate disc, gravitational instabilities in the outer disc, and thermal instabilities in the innermost disc. We intend to test this hypothesis by combining one-dimensional convective, vertical structure models with 1D time-dependent, radial diffusion models for the evolution of the disc in the vicinity of the star. Here we comment on our first results.